2014
DOI: 10.1111/imm.12319
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic activity of an interleukin‐4/interleukin‐13 dual antagonist on oxazolone‐induced colitis in mice

Abstract: SummaryInterleukin-4 (IL-4) and IL-13 are critical drivers of immune activation and inflammation in ulcerative colitis, asthma and other diseases. Because these cytokines may have redundant function, dual targeting holds promise for achieving greater efficacy. We have recently described a bifunctional therapeutic targeting IL-4 and IL-13 developed on a novel protein scaffold, generated by combining specific binding domains in an optimal configuration using appropriate linker regions. In the current study, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 53 publications
0
39
0
Order By: Relevance
“…Thorough elucidation of these groups of markers, or panels, has revealed that these phenotypes are distinguished by expression differences in chemokines, chemokine receptors, enzymes, costimulatory molecules, Toll receptors, cytokines, and cytokine receptors. [39][40][41][42][43] M1 macrophages express inducible nitric oxide synthase (iNOS), the primary marker that confirms the response of these cells in a specific disease (Table 1). [44][45][46] However, a surface marker that defines the identity of M1 macrophages has not yet been identified.…”
Section: Macrophage Phenotypesmentioning
confidence: 92%
“…Thorough elucidation of these groups of markers, or panels, has revealed that these phenotypes are distinguished by expression differences in chemokines, chemokine receptors, enzymes, costimulatory molecules, Toll receptors, cytokines, and cytokine receptors. [39][40][41][42][43] M1 macrophages express inducible nitric oxide synthase (iNOS), the primary marker that confirms the response of these cells in a specific disease (Table 1). [44][45][46] However, a surface marker that defines the identity of M1 macrophages has not yet been identified.…”
Section: Macrophage Phenotypesmentioning
confidence: 92%
“…As with the failure of anti-IFNγ in CD, this result seems to suggest that blocking a single Th2 cytokine is not sufficient to induce a therapeutic response. Anti-IL-4/13 bi-specific antibodies 81 are in development for asthma, and show therapeutic effects in Th2-associated colitis 82 . Thus, it will be of interest to determine if this approach, or perhaps other combinatorial approaches (for example also targeting IL-5 and/or GM-CSF), may be more broadly therapeutic in UC.…”
Section: Cd4+ T Cells In Ibdmentioning
confidence: 99%
“…Recently, a novel treatment was tested in oxazolone treated mice, utilizing a bifunctional IL-4/IL-13 antagonist, in the hopes that such combinatorial blockade would overcome the redundant effects of these cytokines (29). Binding of IL-13 was accomplished via a derivative of the murine IL-13Ra2 extracellular sequence and of IL-4 via a derivative of rat anti-mouse IL-4 mAb 11B11.…”
Section: Downstream Effectors Of Th2 Immunitymentioning
confidence: 99%